Intersectionality : an intellectual history - Hancock, Ange-Marie (Oxford University Press, 2016)
"Intersectionality theory has emerged over the past thirty years as a way to think about the avenues by which inequalities (most often dealing with, but not limited to, race, gender, class and sexuality) are produced. Rather than seeing such categories as signaling distinct identities that can be adopted, imposed or rejected, intersectionality theory considers the logic by which each of these categories is socially constructed as well as how they operate within the diffusion of power relations. In other words, social and political power are conferred through categories of identity, and these identities bear vastly material effects. Rather than look at inequalities as a relationship between those at the center and those on the margins, intersectionality maps the relative ways in which identity politics create power. Though intersectionality theory has emerged as a highly influential school of thought in ethnic studies, gender studies, law, political science, sociology and psychology, no scholarship to date exists on the evolution of the theory. In the absence of a comprehensive intellectual history of the theory, it is often discussed in vague, ahistorical terms. And while scholars have called for greater specificity and attention to the historical foundations of intersectionality theory, their idea of the history to be included is generally limited to the particular currents in the United States. This book seeks to remedy the vagueness and murkiness attributed to intersectionality by attending to the historical, geographical, and cross-disciplinary myopia afflicting current intersectionality scholarship. This comprehensive intellectual history is an agenda-setting work for the theory"--